Insiang - O'Hara, Mario; Antonio, Lamberto; Baltazar, Conrado; Salvador, Augusto; Azarcon, Minda D.; Tan, Ruby Tiong; Brocka, Lino; Coronel, Hilda; Lisa, Mona; Vernal, Ruel; Cortez, Rez; Ramirez, Marlon; et al. (Cinemanila, 1976)
A beautiful girl gets raped by her mother's lover, and then learns how to exact revenge.